Heavy Metals Need Assistance: The Contribution of Nicotianamine to Metal Circulation Throughout the Plant and the Arabidopsis NAS Gene Family - Bauer, Petra; Schuler, Mara (Frontiers in Plant Science, 2011)
Understanding the regulated inter- and intracellular metal circulation is one of the challenges in the field of metal homeostasis. Inside organisms metal ions are bound to organic ligands to prevent their uncontrolled reactivity and to increase their solubility. Nicotianamine (NA) is one of the important ligands. This non-proteinogenic amino acid is synthesized by nicotianamine synthase (NAS). NA is involved in mobilization, uptake, transport, storage and detoxification of metals. Much of the progress in understanding NA function has been achieved by studying mutants with altered nicotianamine levels. Mild and strong Arabidopsis mutants impaired in nicotianamine synthesis have been identified and characterized, namely nas4x-1 and nas4x-2. Arabidopsis thaliana has four NAS genes. In this review, we summarize the structure and evolution of the NAS genes in the Arabidopsis genome. We summarize previous results and present novel evidence that the four NAS genes have partially overlapping functions when plants are exposed to Fe deficiency and nickel supply. We compare the phenotypes of nas4x-1 and nas4x-2 and summarize the functions of NAS genes and NA as deduced from the studies of mutant phenotypes.